PENGARUH FREKUENSI KOMUNIKASI DENGAN ORANG TUA TERHADAP KESEJAHTERAAN EMOSIONAL ANAK KOS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of communication frequency with parents on the emotional well-being of boarding students based on research data. The research employed a quantitative approach with a correlational design. The sample consisted of 30 boarding students at Universitas Negeri Medan selected through purposive sampling based on specific criteria. Data were collected using a Likert-scale questionnaire developed based on the indicators of the research variables. Data analysis was conducted using both descriptive and inferential statistics, including simple linear regression and Pearson correlation tests.The results indicate that the frequency of communication with parents has a significant effect on the emotional well-being of boarding students (p < 0.05). Furthermore, a strong positive relationship was found between the two variables, with a correlation coefficient of r = 0.632. These findings show that higher communication intensity with parents contributes to improved emotional well-being among students. Therefore, communication with parents plays an important role in maintaining emotional stability among students living independently away from home.